Occurrence of biennial Sporophytes of the Kelp Saccharina japonica in Hokkaido, Japan: Kemunculan Sporofit Dwitahunan Rumput Laut Saccharina japonica di Hokkaido, Jepang - Kawai, Tadashi; Kuribayashi, Takanori (Habitus Aquatica, 2024)
Recent studies suggest that relict communities of Saccharina japonica var. ochotensis are rarely observed in southwestern Hokkaido, where S. japonica. var. religiosa is generally distributed. Previous research has mainly focused on the morphology of these species, and field survey data is very limited. In the present study, relict S. japonica var. ochotensis communities were observed only near the estuaries of larger rivers, specifically in estuarine areas where bedrock is present and the seashore has a gentle gradient slope. The biomass and size (length, width, and weight) of annual and biennial relict S. japonica. var. ochotensis were recorded. The carbon/nitrogen ratio of the kelp sporophytes was analyzed, and relatively lower values were observed in the relict community of this species. This information may help in the maintenance of kelp beds in southwestern Hokkaido and the wise utilization of relict S. japonica var. ochotensis in the estuarine areas of southwestern Hokkaido, Sea of Japan.